An International Consensus on the Appropriate Treatment for Adults with Spinal Deformity: An AOSpine Knowledge Forum Deformity Study. Issue 1 (April 2016) - Berven, Sigurd; Kamper, Steve; Germscheid, Niccole; Dahl, Benny; Shaffrey, Christopher; Lenke, Lawrence; Lewis, Stephen; Cheung, Kenneth M. C.; Alanay, Ahmet; Ito, Manabu; Polly, David; de Kleuver, Marinus
Introduction: Appropriate care for adults with spinal deformity should be responsive to considerations of the patient, care provider, and healthcare system. The healthcare burden of adult spinal deformity is increasing significantly and re-operation rates are high (up to 50%). The objective of this study was to identify goals of care and management strategies that are appropriate, reasonable, and inappropriate to guide decision-making and patients' informed choice. Material and Methods: The AOSpine Knowledge Forum Deformity performed a modified Delphi survey of 53 experienced spine deformity surgeons (panelists) from 24 countries. Panelists rated appropriateness of procedures and management strategies for multiple clinical scenarios. Strategies were rated on a 9-point rating scale, collapsed into three categories: 'inappropriate' - expected negative consequences exceed the expected health benefit; 'reasonable' -balance of risk and benefit is unknown, but there is a reasonable chance of positive benefit; and 'appropriate' -expected health benefit exceeds the expected negative consequences by a wide margin. There were three anonymous web-based surveys and one physical meeting. Consensus was defined as ≥70% agreement. Results: Panelists ranked the most important goals of surgery as; improvement of function, pain, and neural symptoms. Regarding preoperative evaluation, there was consensus that: it is appropriate to record severity and duration of symptoms, previous spinal surgeries, comorbidities (94%), and smoking status (87%) as part of the history; and perform a physical examination including, neurologic examination (96%), vascular status (77%), and hip ROM (92%). Pulmonary and cardiovascular tests are appropriate for patients at risk. It is appropriate to obtain full spine standing radiographs (89%) and MRI for all indications, and BMD (DEXA) for patients with risk factors for osteoporosis (≥89%). Intraoperatively: it is inappropriate to perform a decompression alone where there is a progressive (72%) or large curve (70%) or sagittal imbalance (75%). When long fusion is performed, it is appropriate to instrument to the ilium in large curves, osteoporotic bone, and sagittal imbalance; and inappropriate to fuse to L5 in case of L5-S1 disc degeneration (88%). It is inappropriate to augment the UIV (81%) or UIV+1 (79%) with cement if there is no osteoporosis. Long fusion is appropriate when there is sagittal imbalance (85%) or large curves (87%), when performed; L5-S1 interbody support is appropriate (90%). There was no consensus whether a unilateral decompression alone should be performed in a stable sagittally balanced 30° curve. Grafting with local bone is appropriate, as is neuromonitoring with MEP and SSEP. Postoperatively: mechanical DVT prophylaxis is appropriate for all patients and chemical prophylaxis for high-risk. Return to sedentary work is appropriate within 3 months where < 5 segments are fused. Conclusion: Management of adult spinal deformity is characterized by significant variability. We have been able to identify several pre-, intra- and post-operative management strategies that constitute (in-) appropriate care based on the consensus of experienced surgeons. Decision-making is driven not only by features of the deformity (e.g., curve magnitude, sagittal imbalance), but also by patient characteristics (e.g., osteoporosis, cardiac comorbidities, smoking) and some factors may indicate that surgery is not appropriate.